METROLOGICAL SUPPORT IN MANUFACTURING ENTERPRISES - Akbarjon Umarov; Jamshid Yuldashev (Western European Studies, 2024)
This article compiles information about organizing metrological support in manufacturing enterprises and its importance. It discusses the concept of metrology, standards and methodologies, organizational foundations of metrological support, calibration, and its prospects
Keywords: metrological support; measurements; standards; ISO